Perancangan Meja Edukatif Multifungsi untuk Anak Pra Sekolah Berbasis Pendekatan Partisipatif - Ahmad Afif Ardiansah; Drajad Wibowo; Sutarya Sutarya (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to design a multifunctional educational table for preschool children by considering aspects of ergonomics, safety, educational functions, and material sustainability. The study uses a participatory approach combined with the Design Thinking method through the stages of empathize, define, ideate, prototype, and test. In the empathize stage, the researchers explored user needs through observation and interviews with early childhood teachers to understand the problems that arise when children use conventional tables. The define stage resulted in a problem formulation related to the incompatibility of table dimensions, limited functionality, and lack of safety features. Concept ideation was carried out by producing alternative table designs that are stable, ergonomic, have storage space, and utilize furniture waste as the main material. Next, the researchers created a prototype in the form of a miniature table with dimensions and features tailored to the developmental needs of preschool children. The testing stage showed positive responses from teachers as evaluators, who assessed that the table design met the aspects of safety, functionality, and comfort for children. These results show that the Design Thinking approach is effective in producing educational furniture concepts that meet user needs.